Taiwan’s Battle of Recognition: An analysis of the withdrawal of state recognition in practice - Carhed,Micaela (2020)
Since 2016, seven countries have withdrawn its recognition of Taiwan which have left the contested state with only fifteen diplomatic allies. Consequently, this affects the democracy of 23 million people, and minimizes Taiwan’s ability and cooperation in the global world. The problem derives from when Tsai Ing-wen, the current president of Taiwan and the pro-independence Democratic Progressive Party (DPP) was voted in power in 2016. China has since adopted strategies to make alliances switch recognition, intending to isolate Taiwan until “reunification”. This highlights the problem of subjectiveness of state recognition in practice which this thesis aims to investigate. Accordingly, this thesis is a qualitative comparative case study that has employed a theoretical framework of that the practice of recognition stems from power politics and national interests, by looking at the cases of the Dominican Republic and Honduras. The analysis and discussion explores the underlying factors to why the Dominican Republic withdrew from recognition in 2018, while Honduras still is an ally to Taiwan by looking at domestic politics and the relation to Great Powers such as China and the U.S. Based on the findings, this thesis argues, within its aims and limitations, that the decision to withdraw recognition from contested states is foremost based on changes in their economic interests, and pressure from Great Powers.
Keywords: State recognition; Taiwan; Honduras; Dominican Republic; Power Politics; Diplomatic Allies